Exosomes from human umbilical cord mesenchymal stem cells promote the growth of human hair dermal papilla cells - Yu-Cheng Chen; Wei-Cheng Tsai; Zhi-Xiang Li; Wan-Jung Lin; Hao-Yu Lin; Yi-Ju Hsieh; Kai-Hsuan Wang; You-Yan Chen; Tsong-Long Hwang; Tzou-Yien Lin (PLoS ONE, 2025)
Human hair dermal papilla cells (HHDPCs) play a significant role in hair growth. This study found that human umbilical cord mesenchymal stem cell-derived exosomes (UC-MSC-Es) effectively enhanced cell growth of HHDPCs. UC-MSC-Es has a size range of 30–180 nm and expression of CD9, CD63, CD81, CD73, and TSG101. UC-MSC-Es significantly increased cell populations of HHDPCs in the S and G2/M phases. UC-MSC-Es also increased the expression of cell cycle-related proteins, β-catenin, and cyclin D1. Further mechanistic studies demonstrated that UC-MSC-Es promoted the phosphorylation of Akt and GSK-3β, and the inhibition of PI3K and Akt reduced the proliferative effects of UC-MSC-Es. Collectively, these findings suggest that UC-MSC-Es have a potential effect in treating hair loss through modulating PI3K and Akt-dependent pathways in HHDPCs.